Etno Stilistika dalam Kumpulan Puisi Bantalku Ombak Selimutku Angin Karya Zawawi Imron - Kumaidi (Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study analyzes ethno-stylistic elements in the poetry collection Bantalku Ombak Selimutku Angin by Zawawi Imron. This study focuses on how the linguistic characteristics, culture, and local values of the Madurese community are revealed through the language style, diction, and imagery of the poems. The method used is descriptive qualitative analysis with ethno-stylistic approach to identify linguistic peculiarities and local wisdom in the poetry text. The results show that Zawawi Imron utilizes metaphors, natural symbols, and Madurese vocabulary to convey cultural identity, spirituality, and the harmonious relationship between humans and nature. This research also reveals how the poem's stylistics reflect the philosophical and socio-religious values of the Madurese coastal community. The findings enrich the understanding of ethnic literature and the role of poetry as a medium of cultural preservation.